Fertility Regulating Activities of Some Selected Sri Lankan Marine Red Algae - Premakumara, G.A.S. (Faculty of Science, University of Colombo, 1995)
Five different varieties of marine red algae : Gelidiella acerosa, Gracilaria corticata, Gelidium crinale, Jania sp. and Gracilaria sp3, were collected from coastal waters of Southern Sri Lanka and extracted with 1:1 methanol- methylene chloride. Resulting crude extracts (CE), those which had a yield of > 2 g/kg : Gracilaria corticata, Gelidiella acerosa and Jania sp were coprecipitated with polyvinylpyrrolidone and tested for post coital contraceptive activity in pregnant rats at doses of 500 and 1000 mg/kg/ml/day through oral intubation from day 1 to day 7 of pregnancy.